Genome-wide identification and analysis of the NLR gene family in Medicago ruthenica - Tong, Chunyan; Zhang, Yutong; Shi, Fengling (Frontiers in Genetics, 2023)
Medicago ruthenica, an important forage in the legume family, possesses high nutritional value and carries abundant tolerance genes. In this study, based on the whole genome data of M. ruthenica we performed a genome-wide analysis of the nucleotide binding site-leucine-rich repeat receptor (NLR) gene family that is the largest family of plant disease resistance genes (R genes). A total of 338 NLR genes were identified from the M. ruthenica genome, including 160 typical genes that contained 80 coiled-coil (CC)-NBS-LRR (CNL), 76 Toll/Interlukin-1 receptor (TIR)-NBS-LRR (TNL) and four resistance to powdery mildew 8 (RPW8)-NBS-LRR (RNL) subclasses gene and 178 atypical NLR genes encoding proteins without at least one important domain. Among the eight chromosomes, M. ruthenica chromosomes 3 and 8 contain most of the NLR genes. More than 40% of all NLR genes were located on these two chromosomes, mainly in multigene clusters. NLR proteins of M. ruthenica had six highly conserved motifs: P-loop, GLPL, RNBS-D, Kinase-2, RNBS-C and MHDV. Phylogenetic analysis revealed that the NLR genes of M. ruthenica formed three deeply separated clades according to N-terminal domain of proteins encoded by these genes. Gene duplication and syntenic analysis suggested that M. ruthenica NLR genes had four gene duplication types, i.e., tandem, proximal, dispersed, and segmental duplicates, which involved 189, 49, 59 and 41 genes, respectively. A total of 41 segmental duplication genes formed 23 NLR gene pairs located on syntenic chromosomal blocks that were mainly between chromosomes 6 and 7. In addition, syntenic analysis between M. truncatula and M. ruthenica was carried out and found that 193 gene pairs located on syntenic chromosomal blocks of the two species. The expression analysis of M. ruthenica NLR genes showed that 303 (89.6%) of NLR genes could be expressed in different varieties. Overall, the full NLR profile of the M. ruthenica genome was provided in this study, which was an important resource for mining disease-resistant genes and disease resistance breeding.